2004
DOI: 10.1063/1.1712008
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric response of sputtered transition metal oxides

Abstract: We have investigated the dielectric properties of thin layers of five oxides of transition metals (Ta 2 O 5 , HfO 2 , ZrO 2 , (ZrO 2 ) 0.91 (Y 2 O 3 ) 0.09 , and Sn 0.2 Zr 0.2 Ti 0.6 O 2 ) sputtered from ceramic targets at different pressures. We find that layers deposited at low pressure behave as expected from literature, whereas layers deposited at high pressure all exhibit an anomalous dielectric response similar to that reported for the so-called ''colossal'' dielectric constant materials. The characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Several transition metal oxides, such as ZrO 2 and HfO 2 have been studied as alternative high-dielectric constant thin-film materials for replacement of SiO 2 layers in thin-film microdevices [2,5,7]. Recently, thin films of rare earth oxides (REO) have also been investigated as a new, alternative and perspective group of materials for different thin-film applications [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transition metal oxides, such as ZrO 2 and HfO 2 have been studied as alternative high-dielectric constant thin-film materials for replacement of SiO 2 layers in thin-film microdevices [2,5,7]. Recently, thin films of rare earth oxides (REO) have also been investigated as a new, alternative and perspective group of materials for different thin-film applications [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years various experimental studies in search of dielectric materials for integrated optoelectronic and electronic devices have been conducted [1][2][3][4][5][6][7][8]. These applications utilize dielectric materials mainly in thinfilm forms.…”
Section: Introductionmentioning
confidence: 99%
“…At the low temperature reference of 10 K, E g is only about 3 eV for aTa48O120 with the PBE functional, while E g is nearly 4.5 eV with the HSE06 functional. Experimentally reported values for the Ta 2 O 5 E g range from 3.9 to 5.28 eV [18,19], but the average value is about 4 eV; this wide range is typical of many dielectrics and is a result of the variability in dielectric quality and sometimes band gap definition. As temperature increases, the E g for both functionals decreases and the corresponding step function in () softens.…”
Section: Metallic Tamentioning
confidence: 99%
“…Since high-k capacitor dielectrics are the most common application of Ta 2 O 5 to date, many studies in recent years focused on the breakdown and leakage characteristics of a-Ta 2 O 5 to assess the feasibility of incorporation in integrated circuit manufacturing. The work of Fleming et al [18] concluded that O vacancy (V O ) defect concentrations near metal-oxide interfaces are an essential contributor to spurious Ta 2 O 5 leakage currents, while Iosad et al [19] attributed the variability in dielectric response of several transition metal oxides (TMOs), including Ta 2 O 5 , to a dopant-like behavior that depends on the concentration of quenched-in vacancies. Nakamura et al [20] provided one of the first studies of V O aggregation, which is likely an essential mechanism of conductivity modulation.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation